Improving FLAIR SAR efficiency at 7T by adaptive tailoring of adiabatic pulse power through deep learning B1+ estimation. Issue 5 (23rd November 2020) - Abbasi‐Rad, Shahrokh; O'Brien, Kieran; Kelly, Samuel; Vegh, Viktor; Rodell, Anders; Tesiram, Yasvir; Jin, Jin; Barth, Markus; Bollmann, Steffen
Abstract : Purpose: The purpose of this study is to demonstrate a method for specific absorption rate (SAR) reduction for 2D T2 ‐FLAIR MRI sequences at 7 T by predicting the required adiabatic radiofrequency (RF) pulse power and scaling the RF amplitude in a slice‐wise fashion. Methods: We used a time‐resampled frequency‐offset corrected inversion (TR‐FOCI) adiabatic pulse for spin inversion in a T2 ‐FLAIR sequence to improve B 1 + homogeneity and calculated the pulse power required for adiabaticity slice‐by‐slice to minimize the SAR. Drawing on the implicit B 1 + inhomogeneity in a standard localizer scan, we acquired 3D AutoAlign localizers and SA2RAGE B 1 + maps in 28 volunteers. Then, we trained a convolutional neural network (CNN) to estimate the B 1 + profile from the localizers and calculated pulse scale factors for each slice. We assessed the predicted B 1 + profiles and the effect of scaled pulse amplitudes on the FLAIR inversion efficiency in oblique transverse, sagittal, and coronal orientations. Results: The predicted B 1 + amplitude maps matched the measured ones with a mean difference of 9.5% across all slices and participants. The slice‐by‐slice scaling of the TR‐FOCI inversion pulse was most effective in oblique transverse orientation and resulted in a 1 min and 30 s reduction in SAR induced delay time while delivering identical image quality. Conclusion: We propose a SAR reduction technique based on the estimation of B 1 + profiles from standard localizer scans using a CNN and show that scaling the inversion pulse power slice‐by‐slice for FLAIR sequences at 7T reduces SAR and scan time without compromising image quality. Abstract : Click here for author‐reader discussions